2007
DOI: 10.2174/187461360701011106
|View full text |Cite
|
Sign up to set email alerts
|

Early Impact and Performance Characteristics of an Established Anal Dysplasia Screening Program: Program Evaluation Considerations

Abstract: Abstract:Background: Screening for invasive anal cancer and its precursors is being increasingly advocated as a response to increasing incidence among HIV-infected persons. We implemented a comprehensive screening program in 2001 and report our early experience to inform monitoring and evaluation of such programs. Our research aims were: (1) to estimate incidence of and mortality from invasive anal cancer (IAC) before (1995)(1996)(1997)(1998)(1999)(2000) and after (2001)(2002)(2003)(2004)(2005) screening progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…14 Matthews and colleagues 14 found that the percentage of patients receiving anal cancer screening via anal cytology was 73% by the end of the 5-year study period. As the University of Colorado's anal health program continues to expand, it is anticipated that the anal cancer screening rate will approach that in other HIV treatment centers with regular access to anal dysplasia specialists.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Matthews and colleagues 14 found that the percentage of patients receiving anal cancer screening via anal cytology was 73% by the end of the 5-year study period. As the University of Colorado's anal health program continues to expand, it is anticipated that the anal cancer screening rate will approach that in other HIV treatment centers with regular access to anal dysplasia specialists.…”
Section: Resultsmentioning
confidence: 99%
“…9,10 Therefore, some experts have advocated for early identification of anal cancer as a way of improving survival and outcomes for persons diagnosed with SCCA. 8,[11][12][13][14] The development of SCCA has been linked to the precursor lesion of anal intraepithelial neoplasia (AIN). 15 This is similar to cervical intraepithelial neoplasia (CIN), the precursor for cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Comparable analyses for other groups, including women, have not been performed. A single-center study of the early impact and performance of an established anal dysplasia screening program (including 8.4% women) over a follow-up period of 10 years revealed screening detected earlier disease (stage migration); however, the overall incidence rate of invasive anal cancer did not change [24].…”
Section: Anal Carcinomamentioning
confidence: 99%
“…Screening for dysplasia and early anal cancer without treatment of dysplasia has not been shown to reduce anal cancer rates (Mathews, Caperna, Cachay, & Cosman, 2007). Two main issues arise regarding treatment of anal dysplasia when it is discovered in HIV-infected MSM:…”
Section: Treatment For Anal Dysplasiamentioning
confidence: 99%